Process-Based Key Performance Indicators to Improve the Engineering Division Performance in Indonesian National EPC Company - Anang Wirdianto; Ayomi Dita Rarasati (Journal of International Conference Proceedings (JICP), 2019)
Along with the growing competition and technological challenges in the increasingly complex construction industry in Indonesia, Indonesian national companies need to have a key performance indicator (KPI) which is a benchmark for success in order to face the competition. The aim of this study is to obtain engineering performance indicators that are in line with the companies’ objectives. KPI development is based on engineering division work process and will involve the internal department stakeholders who are directly related to the engineering division Qualitative analysis is conducted to obtain performance indicators and proceed with the measurement method.